Alleviating effect of vine tea on Aeromonas hydrophila infection revealed by small RNA transcriptome analyses of loach liver - Lai, Wenqing; Qiu, Yuqin; Pan, Shengnan; Wan, Aijun; Wang, Xueyang; Lv, Dingding; Dai, Lishang (Frontiers in Immunology, 2025)
Vine tea (Ampelopsis grossedentata) is a widely used Chinese herb with a long history of application in southern China, known for its notable anti-infective, antibacterial and immunomodulatory pharmacological properties. It has potential for application in aquaculture as an inexpensive and readily available dietary supplement, promoting growth, antioxidant activity, and immune regulation in fish. However, there have been very few studies investigating the effects of vine tea on fish miRNAs. Loach is an economically important freshwater fish species, highly valued for its delicious flavor, but research on its miRNA relatively limited. To examine immune-related miRNAs in loach and to further determine the antibacterial immune mechanisms of vine tea, we performed small RNA sequencing analysis of loach liver tissue before and after treatment with vine tea extract. The results showed that vine tea could affect the antibacterial immune activity of loach through the miRNA regulation. A total of 25 differentially expressed miRNAs were identified in liver tissues, and KEGG pathway analysis revealed that most of these miRNAs were involved in innate immune responses such as autophagy, lysosomes, endocytosis, and pattern receptor signaling pathways. To the best of our knowledge, this is the first study to profile miRNA expression in loach after treatment with vine tea extract. This work deepens the understanding of the role of loach miRNAs in the immune system and opens new prospects for application of vine tea in aquaculture.